SINERGITAS AGAMA DAN MEDIA DALAM MASA KONVERGENSI MEDIA INDONESIA - Chotib, Nur Sofian (Program Studi Komunikasi dan Penyiaran Islam, 2025)
Religion ideally teaches noble and noble values, but in the current era of media convergence, religion that was once sacred and had a special place for its adherents has now shifted to become a lucrative business for religious capitalists, coupled with the rapid advancement of technology that has resulted in media convergence that has given birth to new media that has succeeded in changing the paradigm of society in viewing religion, religion is no longer a taboo that is only limited to people who have a certain capacity who have the right to convey religious messages and modify them. Now anyone can do it regardless of the underlying motivation, religion has now lost its original form. That is the need for synergy in the development between religion and media so that they complement each other for noble and noble goals.